Investigating associations between physical activity-related neighborhood built environment features and child weight status to inform local practice. (February 2021) - Carlson, Jordan A.; Shook, Robin P.; Davis, Ann M.; Papa, Amy; Steel, Chelsea; Bejarano, Carolina; Noel-MacDonnell, Janelle R.; Summar, Shelly; Dean, Kelsey; Hampl, Sarah E.
Abstract: Despite evidence of the importance of neighborhood built environment features in relation to physical activity and obesity, research has been limited in informing localized practice due to small sample sizes and limited geographic coverage. This demonstration study integrated data from a local pediatric health system with nationally available neighborhood built environment data to inform local decision making around neighborhood environments and childhood obesity. Height/weight from clinic visits and home neighborhood measures from the U.S. Environmental Protections Agency and WalkScore were obtained for 15, 989 6–17 year olds. Multilevel models accounted for the nested data structure and were adjusted for neighborhood income and child sociodemographics. In 9–17 year olds, greater street connectivity and walkability were associated with a 0.01–0.04 lower BMIz (Ps = .009-.017) and greater residential density, street connectivity, and walkability were associated 5–7% lower odds of being overweight/obese (Ps = .004-.044) per standard deviation increase in environment variable. 45.9% of children in the lowest walkability tertile were overweight or obese, whereas 43.1% of children in the highest walkability tertile were overweight or obese. Maps revealed areas with low walkability and a high income-adjusted percent of children overweight/obese. In the Kansas City area, data showed that fewer children were overweight/obese in more walkable neighborhoods. Integrating electronic health records with neighborhood environment data is a replicable process that can inform local practice by highlighting the importance of neighborhood environment features locally and pointing to areas most in need of interventions. Highlights: A replicable approach for integrating health records and walkability data is presented. Fewer children were overweight or obese in more walkable neighborhoods. Investigating walkability and obesity using health records can inform local practice.